2008
DOI: 10.1161/circulationaha.107.746537
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Reduction by Ivabradine Reduces Oxidative Stress, Improves Endothelial Function, and Prevents Atherosclerosis in Apolipoprotein E–Deficient Mice

Abstract: Background— Elevated heart rate is associated with increased cardiovascular morbidity. We hypothesized that selective heart rate reduction may influence endothelial function and atherogenesis and tested the effects of the I (f) current inhibitor ivabradine in apolipoprotein E–deficient mice. Methods and Results— Male apolipoprotein E–deficient mice fed a high-cholesterol diet were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
190
3
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(232 citation statements)
references
References 49 publications
18
190
3
21
Order By: Relevance
“…Despite this, a recent study found that ivabradine did not have beneficial effects in patients with stable coronary artery disease but without heart failure 10 , suggesting that its vasculoprotective effects may be restricted to patients with heart failure. The mechanism for the protective effects of ivabradine has been studied using animal models [11][12][13][14] . The administration of ivabradine reduced experimental atherosclerosis in hyperlipidaemic murine 13 and rabbit models 14 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, a recent study found that ivabradine did not have beneficial effects in patients with stable coronary artery disease but without heart failure 10 , suggesting that its vasculoprotective effects may be restricted to patients with heart failure. The mechanism for the protective effects of ivabradine has been studied using animal models [11][12][13][14] . The administration of ivabradine reduced experimental atherosclerosis in hyperlipidaemic murine 13 and rabbit models 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism for the protective effects of ivabradine has been studied using animal models [11][12][13][14] . The administration of ivabradine reduced experimental atherosclerosis in hyperlipidaemic murine 13 and rabbit models 14 . However, molecular targets of ivabradine have not been identified in vascular cells and the atheroprotective effects of ivabradine are not due to a lipid-lowering effect of ivabradine, since the drug had no effects on cholesterol levels [11][12][13] .…”
Section: Introductionmentioning
confidence: 99%
“…В исследованиях на животных получены плейо-тропные эффекты ивабрадина -такие, как антиокси-дантный, антиатеросклеротический, улучшение эндотелиальной дисфункции. Так в работе F. Custodis et al установлено, что снижение ЧСС с помощью 6-недельного применения ивабрадина уменьшает выработку маркеров оксидативного стресса, улуч-шает функцию эндотелия и уменьшает размеры ате-росклеротической бляшки у мышей независимо от АД и уровня липидов [26]. M. Baumh kel et al пока-зали, что у мышей на фоне эндотелиальной дисфунк-ции, индуцированной диетой с высоким содержа-нием холестерина, 3-месячная терапия ивабрадином способствует уменьшению размеров атеросклероти-ческих бляшек и улучшению эндотелиальной дис-функции [27].…”
Section: Discussionunclassified
“…Their effects are amplified when production of atheroprotective endothelial nitric oxide (NO) is reduced by EC dysfunction. Both increased ROS and reduced endothelial NO [14][15][16][17][18][19] have been implicated in accelerating plaque progression in Apoe -/-mice and are represented in the model.…”
Section: Oxidative Stressmentioning
confidence: 99%